2017
DOI: 10.3343/alm.2017.37.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Telomere Lengths and Telomerase Activity in Myelodysplastic Syndrome

Abstract: BackgroundTelomere shortening is thought to be involved in the pathophysiology of myeloid malignancies, but telomere lengths (TL) during interphase and metaphase in hematopoietic malignancies have not been analyzed. We aimed to assess the TLs of interphase and metaphase cells of MDS and telomerase activity (TA) and to find out prognostic significances of TL and TA.MethodsThe prognostic significance of TA by quantitative PCR and TL by quantitative fluorescence in situ hybridization (QFISH) of interphase nuclei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…In a recent study [ 72 ], no significant correlation between telomerase activity and TL could be found in MDS patients ( n = 53), and for overall survival, there was no significant difference between high and low telomerase activity according to the log rank method. However, patients with high telomerase activity showed a significantly shorter interval for transformation to acute leukemia ( p = 0.010), suggesting high telomerase activity as a poor prog­nostic marker in MDS.…”
Section: Myelodysplastic Syndrome (Mds)mentioning
confidence: 96%
“…In a recent study [ 72 ], no significant correlation between telomerase activity and TL could be found in MDS patients ( n = 53), and for overall survival, there was no significant difference between high and low telomerase activity according to the log rank method. However, patients with high telomerase activity showed a significantly shorter interval for transformation to acute leukemia ( p = 0.010), suggesting high telomerase activity as a poor prog­nostic marker in MDS.…”
Section: Myelodysplastic Syndrome (Mds)mentioning
confidence: 96%
“…Other cancers for which short telomere length can be used as a prognostic indicator include non-small-cell lung cancer, myelodysplastic syndromes (MDS) and multiple myeloma [ 127 , 128 , 129 , 130 ]. This finding was particularly striking in Multiple Myeloma, considering median telomere length was measured from a mixed population of cells extracted from bone marrow [ 129 ].…”
Section: Telomere Length As a Prognostic Marker In Cancermentioning
confidence: 99%
“…Furthermore, it is very labor-intensive to generate a sufficient number of karyograms for measurements and there may be a selection bias with respect to the cell types that are mitotically active in the sample. These types of problems can be overcome by quantitative fluorescence in situ hybridization of interphase nuclei (iQFISH) measuring relative telomere content in interphase nuclei [ 22 ]. We have previously utilized this T/C iQFISH method to investigate telomeres in a patient’s bone marrow cells with or without genomic aberrations in the same sample [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…The bone marrow sample of Case 2 and the age-matched control were hybridized with a Cy3-labeled PNA telomere probe and an FITC-labeled PNA centromere 2 probe. Images of at least 250 nuclei in each case were captured automatically and analyzed by the ISIS-Telomere module [ 19 , 22 ]. The software calculates a relative telomere to centromere (T/C) fluorescence ratio unit (FRU) multiplied by 100 [ 19 , 20 ].…”
Section: Resultsmentioning
confidence: 99%